mcr-1 in Carbapenemase-Producing Klebsiella pneumoniae in Hospitalized Patients, Portugal, 2016-2017 - Mendes, AC (2018)
We describe a hospital-based outbreak caused by multidrug-resistant, Klebsiella pneumoniae carbapenemase 3-producing, mcr-1-positive K. pneumoniae sequence type 45 in Portugal. mcr-1 was located in an IncX4 plasmid. Our data highlight the urgent need for systematic surveillance of mcr-1 to support adequate therapeutic choices in the nosocomial setting.